2013
DOI: 10.1177/0034355213512210
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Depressive Symptoms Among Individuals With Spinal Cord Injuries

Abstract: Depression is a serious mental disorder that is estimated to affect roughly 16% of individuals at some point in their lives (National Institute of Mental Health, 2005). In any one-year period in the United States, mood disorders affect 11% of adults and 6% of children (Woo & Keating, 2008). Furthermore, rates of depression are increasing, while the age of onset is decreasing. Some researchers have described this era as "the age of melancholy" (Schotte, Van De Bossche, Doncker, Claes, & Cosyns, 2006). These au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Concerning factors related to depression, social support, and coping strategies among individuals with spinal injury after hospitalization, our multivariate analysis revealed severity of disability, the guidance provision, the fighting spirit strategy, and the social reliance strategy to be independently associated with depression. These findings are consistent with those of previous studies that found severity of disability 23 , social support 24,25,26 , and coping strategies 11,17 to be factors that significantly influenced depression among individuals with spinal injury. Khazaeipour, et al 23 found a high likelihood of the development of depression among individuals with paraplegia.…”
Section: Original Article Smjsupporting
confidence: 92%
See 2 more Smart Citations
“…Concerning factors related to depression, social support, and coping strategies among individuals with spinal injury after hospitalization, our multivariate analysis revealed severity of disability, the guidance provision, the fighting spirit strategy, and the social reliance strategy to be independently associated with depression. These findings are consistent with those of previous studies that found severity of disability 23 , social support 24,25,26 , and coping strategies 11,17 to be factors that significantly influenced depression among individuals with spinal injury. Khazaeipour, et al 23 found a high likelihood of the development of depression among individuals with paraplegia.…”
Section: Original Article Smjsupporting
confidence: 92%
“…Concerning social support, previous studies found a greater amount of social support to be associated with a lower depression score. 26,25 Social support that emphasizes problem management may influence a reduction in depression during the patient's adjustment to each stage of physical impairment -especially social support provided by professionals and families because these types of support positively influence SCI patient well-being. 26 Concerning coping strategies, studies from Sweden 11 and Turkey 17 found that effective coping strategies associated with lower depression scores.…”
Section: Original Article Smjmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to finding connections between forgiveness and stress, research has found perceived stress to be associated with wellbeing outcomes such as life satisfaction (Rey & Extremera, 2015), psychological wellbeing (He et al, 2018), and perceived physical health (Homan & Sirois, 2017). Specific to people with SCI, catastrophizing and stress are both positively related to depressive symptoms (O’Shea et al, 2014) and perceived stress is negatively related to perceived quality of life (Smedema et al, 2010). Numerous studies have also found stress to be negatively related to life satisfaction in people with SCI (Kraft & Dorstyn, 2015; Migliorini et al, 2008).…”
Section: Perceived Stress and Wellbeingmentioning
confidence: 99%
“…Spinal cord injury (SCI) is an extraordinarily challenging event for sufferers who often develop different levels of physical loss, psychological difficulties, and social limitations. Bio‐psychosocial models of SCI emphasize dynamic interactions between physical, psychological, and social factors, which highlight the importance of and a need for psychosocial interventions during the rehabilitation process (O'Shea & Smedema, ). Many health systems globally put much emphasis and effort in these patients’ medical rehabilitation, with comprehensive medical treatment programs addressing their physical complications, exercise and mobility, and daily functioning (Middleton, Perry, & Craig, ).…”
Section: Introductionmentioning
confidence: 99%